Integrative delimitation of two new, meiobenthic species of flatworms from Panama, constituting two new genera of marine triclads (Platyhelminthes, Tricladida, Maricola) - Sluys, Ronald; Vila-Farré, Miquel; Laumer, Christopher E. (Zootaxa, 2025)
Although platyhelminths are common members of marine interstitial communities, the number of meiofaunal marine triclads known at present is rather limited. Here, we describe two new monotypic genera of interstitial marine triclads from Panama. In order to shed light on their phylogenetic and taxonomic position, we have followed an integrative approach that includes not only comparative analysis of their morphology but molecular phylogenetic placement with small and large rDNA sequences. Our phylogenies were broadly congruent with recently published molecular phylogenies of the marine triclads. The two new genera appeared not to be closely related, but, nevertheless, do share several morphological features, such as the presence of (1) a secondary gonopore, (2) a glandular region traversed by many septa in a large portion of the penis, (3) a copulatory bursa connected with the secondary gonopore, and (4) two retinal cells per eyecup. However, they do also differ considerably from each other. The following combination of factors made it impossible to assign the two new genera to any of the higher categories within the suborder of the marine triclads: (a) a unique combination of features present in each of the genera that does not fit into any of the current family diagnoses, (b) their present position in the phylogenetic tree, (c) the mismatch between the topologies of the molecular phylogenetic trees and the current taxonomic classification within the suborder. Therefore, the two taxa are classified as genera incertae sedis, pending a broader revision of the taxonomy of Maricola.